KONSEP SABAR DALAM AL-QURAN DAN KONTEKSTUALISASINYA DALAM TUJUAN HIDUP MANUSIA MELALUI PENDIDIKAN - Sukino, Sukino (Ruhama : Islamic Education Journal, 2018)
This article aims to explain two important things, first the concept of patience; second, patience contextualization in the purpose of human life through education. Patience is an inner condition that becomes the determination of the achievement of human life goals. patience is the ability to organize, control, direct behavior, feelings and actions and overcome various difficulties comprehensively, meaning able to capture the problem well and broad information to face problems, while integrative means able to see the problem in an integrated manner. Contextualization of the concept of patience can be realized in all actions of educators and learners since the beginning of education begins, both at home and at school. Patient attitudes that are experienced by educators and learners are the key to success in achieving life goals.Key Word: The Concept of Patience, Purpose of life, education